Implementasi Magic Multiplication Box sebagai Media Berhitung Perkalian di Kelas III Sekolah Dasar Negeri Mranggen 01 Kecamatan Polokarto Kabupaten Sukoharjo - Sukmawati, Elza Nabillah; Dwi Anggraeni Siwi (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to examine the implementation of the Magic Multiplication Box as a medium for teaching multiplication to third-grade students at Mranggen 01 Public Elementary School, Polokarto District, Sukoharjo Regency. The Magic Multiplication Box is a visual aid used as a learning tool for basic multiplication (1–10) in third-grade classrooms. This qualitative research employed data collection techniques such as observation, interviews, and documentation. The research subjects included the third-grade teacher and three students from Mranggen 01 Public Elementary School. The findings indicate that: The implementation of the Magic Multiplication Box as a multiplication learning medium helped students grasp the concept of multiplication through the visualization of repeated addition. Out of 17 students, there was an improvement in their understanding and ability to solve problems independently. The third-grade students showed a positive response, displaying enthusiasm and active participation during lessons using the Magic Multiplication Box. However, challenges were identified, such as the limited availability of only one teaching aid and the need for further development in the design and features of the Magic Multiplication Box.